2009
DOI: 10.1111/j.1365-2958.2009.06897.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical analysis of the serine/threonine protein kinases PknA, PknB, PknG and PknL of Corynebacterium glutamicum: evidence for non‐essentiality and for phosphorylation of OdhI and FtsZ by multiple kinases

Abstract: We previously showed that the 2-oxoglutarate dehydrogenase inhibitor protein OdhI of Corynebacterium glutamicum is phosphorylated by PknG at Thr14, but that also additional serine/threonine protein kinases (STPKs) can phosphorylate OdhI. To identify these, a set of three single (ΔpknA, ΔpknB, ΔpknL), five double (ΔpknAG, ΔpknAL, ΔpknBG, ΔpknBL, ΔpknLG) and two triple deletion mutants (ΔpknALG, ΔpknBLG) were constructed. The existence of these mutants shows that PknA, PknB, PknG and PknL are not essential in C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 39 publications
6
68
0
Order By: Relevance
“…In previous reports, we have characterized the four STPKs of C. glutamicum and demonstrated that the PknA and PknB kinases were involved in cell division and PG biosynthesis. Moreover, different STPK substrates have been identified and characterized as proteins involved in cell division and PG biosynthesis thus confirming the critical role of Ser/Thr phosphorylation in regulating such pathways (34,62). Therefore, we hypothesized that RsmP could be regulated via STPK phosphorylation, and this was confirmed in this study by evidence that corynebacterial PknA and PknL can phosphorylate RsmP.…”
Section: Discussionsupporting
confidence: 69%
“…In previous reports, we have characterized the four STPKs of C. glutamicum and demonstrated that the PknA and PknB kinases were involved in cell division and PG biosynthesis. Moreover, different STPK substrates have been identified and characterized as proteins involved in cell division and PG biosynthesis thus confirming the critical role of Ser/Thr phosphorylation in regulating such pathways (34,62). Therefore, we hypothesized that RsmP could be regulated via STPK phosphorylation, and this was confirmed in this study by evidence that corynebacterial PknA and PknL can phosphorylate RsmP.…”
Section: Discussionsupporting
confidence: 69%
“…For instance, although StkP efficiently phosphorylates FtsZ in vitro, negligible (if any) differences in phosphorylation patterns were observed using anti-pThr antibodies after immunoprecipitation in stkP mutants (34). However, FtsZ also was shown to be phosphorylated in Corynebacterium glutamicum, Streptomyces coelicolor, and Streptococcus agalactiae (20,51,52), suggesting that STK-dependent phosphorylation of FtsZ is widespread in Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…While eSTKs regulate many essential bacterial processes, most eSTKs are not themselves essential, with M. tuberculosis PknA and PknB being prominent exceptions (47,75,150). The reported essentiality of the C. glutamicum PknA and PknB homologs appears to be strain specific (49,157). While mutations in B. subtilis PrkC (50,159) or in the eSTKs of several streptococcal species (68,72,144) revealed that these proteins are not, strictly speaking, essential, they led to significant stationary-phase survival defects.…”
Section: Estks In Bacteriamentioning
confidence: 99%